(untitled) (Journal of Tikapur Multiple Campus, 2018)
Barghar system is the traditional and indigenous organizational system in the Tharu community of Tarai region of Nepal. Traditionally, Barghars perform the role of adjudicator of community disputes and issue decisions and verdicts, generally with community consultations. Other functions are to determine the festival calender and perform rituals. They lead the selection of persons with religious responsibilities and coordinate traditional rituals and pujas (worship). They also manage and facilitate Tharu festivals, dances and marriage ceremonies. This study aims to to describe the organizational and selection procedure of Barghar System in Tharu Community of Kailali district, to identify the role of Barghars in social mobilization of Tharu community and to assess the social mobilization practices of Barghar system in Tharu Community Janaki Rural Municipality. A qualitative approach which used a questionnaire, Focused Group Discussion was used as the main instrument to identify the role of Barghars and social mobilization practices of Barghar system in Tharu Community of Janaki Rural Municipality. 12 Barghars ( 6 ex-barghars and 6 current Barghars) became the respondents from ward no.1 and ward no. 5 for this research. Barghar plays the central role especially the role of executives, directional and managerial in the social mobilization of Tharu community. Roles and responsibilities of Barghars are categorized into various sectors such as administrative, leadership, judicial, ritual and development and planning of the village.